1998
DOI: 10.2337/diacare.21.5.831
|View full text |Cite|
|
Sign up to set email alerts
|

Pubertal Growth in ID DM Is Determined by HbA1c Levels, Sex, and Bone Age

Abstract: We conclude that the magnitude of the pubertal growth spurt is related to HbA1c levels in both sexes, but it is reduced only in girls. This sexual dimorphism cannot be explained by differences in IGF-I levels and may relate to the bone age advance at the onset of puberty in the girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 0 publications
8
61
1
7
Order By: Relevance
“…Although unproven, this sex-related difference in association between adiponectin and adiposity may relate to the timing of accumulation of intra-abdominal fat and greater insulin resistance in females than in males [25] and to the effects of sex steroids [18]. In type 1 diabetes, timing of puberty is altered [26] and BMI and insulin resistance are increased during adolescence, particularly in girls [27,28]. Furthermore, risk of microalbuminuria in female adolescents is associated with higher androgen levels [29].…”
Section: Discussionmentioning
confidence: 99%
“…Although unproven, this sex-related difference in association between adiponectin and adiposity may relate to the timing of accumulation of intra-abdominal fat and greater insulin resistance in females than in males [25] and to the effects of sex steroids [18]. In type 1 diabetes, timing of puberty is altered [26] and BMI and insulin resistance are increased during adolescence, particularly in girls [27,28]. Furthermore, risk of microalbuminuria in female adolescents is associated with higher androgen levels [29].…”
Section: Discussionmentioning
confidence: 99%
“…Healthy females are less insulin-sensitive than healthy males. Such decreased sensitivity is compensated by increased insulin secretion (32). Some studies have also shown that both HbA1c and insulin dose were significantly higher in female patients (14,16,33).…”
Section: Comparison With Other Studiesmentioning
confidence: 98%
“…In agreement with different studies (22) and different cultural backgrounds, pubertal girls presented higher mean A1C values than boys. It has been shown that linear growth might also be impaired in children even when reasonable glycemic control had been achieved (23,24), and this growth pattern is likely to be more pronounced in a setting in which metabolic control is very poor. In fact, most of our children had short stature, which was more pronounced in puberty, in accordance with other studies (25,26).…”
mentioning
confidence: 99%